Enhancing Students’ Creativity in Art Education through Innovative Teaching Methods - Aminova Sabina Anvar qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores strategies for enhancing students’ creativity in art education at the secondary school level through the application of innovative teaching methods. It examines how interactive learning, project-based assignments, the use of technology, and flipped classroom approaches contribute to improving students’ artistic skills, critical thinking, and engagement in lessons. The study also highlights practical recommendations for educators to implement these methods effectively and improve overall learning outcomes.